Sociology Between Science and Knowledge - Iannaccone, Antonio (Italian Sociological Review, 2022)
Since scientists have a difficult task – studying something that everyone already knows or thinks they know – they must laboriously earn (with rigorous research methods) the respect of those intellectuals belonging to different fields, and that of others in general. A respect constrained to the filling of some serious gaps in sociology itself: for example, think of the many investigations that – excessively unbalanced on the theoretical side – show a marked philosophical imprint (and so they create a certain conceptual confusion between different sectors, even if they are connected), or to the sterile methodological disputes between standard and non-standard researchers, or to those studies that hide their shortcomings, their clichés and obvious statements behind rather imaginative words of wisdom or catchy slogans. It is therefore up to sociologists 2.0 to take matters into their own hands and above all their profession, in order to restore the dignity it deserves. They are the ones who will have to become aware of society, without waiting (perhaps in vain) for society to finally become aware of them. And it is still them – above all in Italy where culture remains largely a-sociological – who will have to orient themselves by seeking ever new (innovative) forms of participation and cooperation.